MODEL FOR THE FORMATION OF PROFESSIONAL COMPETENCE IN THE FIELD OF INFORMATION SECURITY AMONG FUTURE ECONOMISTS - Ochilova Gulnoza Odilovna (European Journal of Humanities and Educational Advancements, 2023)
The article discusses the conditions for the creation of a dimensionation of a model of the process of formation of professional competence in the field of information security for future economists in high e reeducation